Ecoepidemiology of Schistosomiasis mansoni in a rural area of Sergipe, Brazil (Research, Society and Development, 2021)
Schistosomiasis mansoni is a severe water-borne parasitic disease which etiological agent is Schistosoma mansoni. Among the municipalities of Sergipe, Malhador, has one of the highest prevalence. The present research intends to describe the echoepidemiology of schistosomiasis mansoni in a rural community.  A cross-sectional epidemiological study was carried out based on primary data resulting from malacological (light exposure technique) and coproscopic (Kato-Katz method) surveys A questionnaire was applied to evaluate the epidemiological variables of interest. In the descriptive data analysis, the software BioEstat (version 5.0) was used. The spatial analysis of the infection distribution in the studied locality was done through TerraView 4.2.0, using the kernel intensity estimator. The statistical analysis was performed through the Chi-Square Test and Multiple Logistic Regression. 95 people participated of the census survey. The prevalence was 45%. As for the parasite load, the mild infection prevailed (53.49%), followed by moderate (37.1%) and high (9.30%). Regarding the dichotomous epidemiological variables analyzed, the time of residence (OR = 11.5114), degree of contact with water (OR = 3.9383), knowledge about the disease (OR = 2.0148) and gender (OR = 1.5141) were highlighted. Nine breeding sites were detected and georeferenced. This study provided information that allows health services and public managers to plan, implement and evaluate the impact of measures to be taken to control the transmission of the disease.